Analisis Variasi Genotipik Bawang Merah | Allium cepa L.| Di Pulau Jawa Menggunakan Penanda ISSR - FITRIANA, NITA; Susandarini, Ratna (Berkala Ilmiah Biologi, 2025)
Shallot (Allium cepa L.) is one of Indonesia's leading agricultural commodities due to their high production. Exports reached USD 6.53 million and have continued to increase over the past decade, making them the fourth-ranked exporter in ASEAN. Its produced in 24 of Indonesia's 34 provinces, with the largest production in Java (Center for Agricultural Data and Information Systems, 2023). Production quality is determined by genotipic variation. This study aimed to analyze the genotipic variation of twelve Allium cepa L. cultivars in Java Island. PCR-ISSR method with 5 random primer (ISSRred20, ISSRed4,ISSRed9,UBC892, and UBC-895) was used to evaluate genotipic variation in Allium. The level of genetic similarity was determined by simple matching coefficient (SSM) and the dendrogram was constructed by clustering analysis using UPGMA. The results of genomic DNA amplification using five primers yielded 40 DNA fragment consisting of 12 monomorphic DNA fragment and 28 polymorphic DNA fragment. Genotypic variation indexes of twelve cultivars were 44.1%. It means had moderate variability because of its had 40-60% similarity. Two clusters were formed. Bauji, Bima, Katumi, Kramat2, Trisula, Kramat1, Pikatan and Tiron had the closest relationship with a similarity value of 64.6%. While the cultivars Sembrani, Maja Cipanas, Mentes and Pancasona had the closest relationship with a similarity value of 66.7% The implications of this research could be based for assembling superior seeds of shallot cultivars in Indonesia to supported national food security for now and in the future.